Are Pre-Service Teachers Ready to Teach? Investigating the Impact of Personality Traits and Communication Skills - Karima Al Kharousi; Astri Yulia; Nur Aida Sabrina bt Mohd Rozi; Puteri Nur Aina bt Abd Malek (English Education Journal: Jurnal Pengembangan Pendidikan dan Pengembangan Pengajaran Bahasa)
Personality traits and communication skills play a major role in a teacher’s ability to deal with students and the classroom environment. Communication skills are also one of the key factors that determine a teacher’s success in conveying knowledge and understanding to students. In the pre-service stage, teachers may receive academic training in academic subjects, but actual preparation for teaching requires more than just knowledge of academic content. This study focuses on a group of pre-service teachers who were undergoing part-time teaching and practical training in a private higher education institution in West Malaysia. The main objective of this study is to understand the relationship between personality traits and communication skills and their impact on pre-service teacher’s preparedness. This study employs a quantitative approach and a cross-sectional design. To collect the data, the survey method was utilized. The survey instrument was adapted from the Big Five Personality Traits Theory, the Communication Skills Scale, and the Teacher Readiness Scale. The survey questionnaire was distributed to 164 pre-service teachers, online via Google Forms. The results of the study exhibit that the Big Five personality traits explain a significant portion (50%) of variance in willingness to teach among preservice teachers. Communication skills, on the other hand, had a smaller influence (39.5%). Additionally, the results indicate that preservice teachers with strong personality traits, such as empathy and patience, in addition to communication skills, are associated with the ability to create and stimulate a safe learning environment for students. Other personality traits such as openness and emotional stability are significant factors influencing teachers’ willingness, mediated by communication skills.